Gizi Seimbang dari Dapur Nusantara : Edukasi dan Berbagi Bubur Manado di RT.01, Kelurahan Selumit - Nurul Hidayat; Gea Dilah Hermila; Muhammad Chaidir; Maria Deslianti Suryani Katim; Nanda Saputra; Noni Haironi; Sindy Arismawati Hasan; Yuniati Yuniati (Jurnal Kemitraan Masyarakat, 2025)
The "Balanced Nutrition from the Archipelago’s Kitchen" initiative is an educational and practical effort aimed at increasing community awareness of the importance of consuming balanced nutritious foods through a local culinary approach. This program was conducted in RT.01, Selumit Urban Village, focusing on nutrition education and the distribution of Bubur Manado (Manado porridge) as an example of a healthy traditional dish. The methods included nutrition counseling, cooking demonstrations, and food distribution to residents. The results showed improved community understanding of balanced nutrition concepts and greater appreciation for traditional Indonesian cuisine as a source of nutritious food. This activity also fostered a sense of solidarity and cooperation among community members. It is hoped that similar programs can serve as a sustainable model for culturally based nutrition education in other communities.